KANTATA NUSA LAWO PENGGABUNGAN MUSIK KANTATA DAN MUSIK KONTEMPORER BERDASARKAN IDIOM MUSIK SANGIHE - Yohan C. Tinungki (SURYA SENI, 2008)
Cantata Nusa Lawo is a musical composition tells about Sangihe area which is a regency in North Sulawesi Province. Nusa Lawo comes from Sangihe language that means many islands, this is because Sangihe geography consists ofmany islands, either little islands or big ones. The livelihood of Sangihe society in religion, social, culture, and geography is told in this work of music Cantata Nusa Lawo. In this work the writer does the best to pour the poetical idea into music either narrative or descriptive.  Cantata music is a musical work that sung and accompanied by instrument. Since 1620 in Italy, cantata is a polite form music but in its main characteristicthere is a series of contrast section, especially resitative, unisono, and aria that before eighteenth century becomes a free movement/self-standing one. Through analyse acts, Cantata Nusa Lawo is made, based on a contemporarysystem among others: tones that move with same intervals (parallelism), mode composition with 6 scales interval which is differed by interval with diatonical mode. There is also changing in symmetrical motives, changing in beat, rhytmicalalteration, melodical alteration, motive contraction perfoming, chromatical expansion of tones, 7 th major accord, 9th mayor, 11th accord, and 13th accord. Contemporary music is not always a new one and new music is not always contemporary.There are two waves that ﬁ ght each other namely innovation wave and simpliﬁ cation wave. When the innovation wave is higher, the music in that time becomes  new music, when retrogretion wave appears, the music will goes backits history steps. The appearance of contemporary music does not free from the inﬂ uence of world development in totality. The contemporary understanding  in music world is more tendency as a new atmosphere discovery that is different with before discovery, this case is caused by technological progress that help the music development and as a result of development of understanding and contemplationsthat give a new concept about music.Keywords: Cantata, Nusa Lawo, Sangihe, and Contemporary